Partnerships in sustainable urban development : experiences from Sweden and Finland - Modarress-Sadeghi, Mitra (My University, 2012)
This thesis examines partnerships in sustainable urban development projects. Achievement of urban development requires the involvement of several parties. The cooperation of the actors of sustainable urban development is achieved by forming partnerships. The purpose of this study is to find solutions and best practices for the management of partnerships in sustainable residential development projects by examining partnerships and their success factors in sustainable urban development. The impact of the roles, responsibilities and interactions of actors taking part in the processes of creating sustainable urban development in outcomes of these development projects and thus on the overall success of accomplishing sustainable development raises the question of how to manage these collaborations. In order to be able to find the best ways of organizing sustainable urban development projects, it is crucial to have the knowledge of how the interactions between all the parties involved in the development can be managed successfully to give the best outcomes. The main research question of this study is: What are the characteristics of successful partnerships in sustainable urban development projects? In order to answer this question, the success factors in partnerships between actors of sustainable urban development are analyzed. In addition, challenges related to these partnerships are examined to get a more comprehensive view of the features of these collaborative ventures and the obstacles that have to be overcome to ensure the successfulness of cooperation. The research approach is multiple case study comprising four cases. The empirical data has been gathered through theme interviews from four different sustainable residential district projects in Sweden and Finland. A comparative analysis of the cases is performed, based on which seven success factors of partnerships in sustainable urban development supported by the prevailing theories are formulated. In addition, challenges faced by projects regarding the partnerships are discussed.